2011
DOI: 10.1039/c1cc10917k
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylation of aromatic carboxylic acids by gold(i)-N-heterocyclic carbene (NHC) complexes

Abstract: A recently isolated gold(I) complex, [Au(IPr)(OH)], permits the transformation of carboxylic acids to the corresponding decarboxylated gold(I)-aryl complex without the use of silver co-catalyst under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 38 publications
2
70
1
2
Order By: Relevance
“…In 2010, we reported a straightforward procedure to obtain stable aryl gold complexes by decarboxylation of (hetero)aromatic carboxylic acids with the Brønsted base [Au(IPr)(OH)] (IPr=1,3‐bis(2,6‐diisopropylphenyl)‐imidazol‐2‐ylidene) complex at low temperature 10. This first insight into the decarboxylation reaction with gold revealed a similar reactivity trend to silver.…”
Section: Methodsmentioning
confidence: 96%
“…In 2010, we reported a straightforward procedure to obtain stable aryl gold complexes by decarboxylation of (hetero)aromatic carboxylic acids with the Brønsted base [Au(IPr)(OH)] (IPr=1,3‐bis(2,6‐diisopropylphenyl)‐imidazol‐2‐ylidene) complex at low temperature 10. This first insight into the decarboxylation reaction with gold revealed a similar reactivity trend to silver.…”
Section: Methodsmentioning
confidence: 96%
“…However, because Au complexes have been regarded inert for the past several decades and also because of the high price of Au catalysts, few studies have been carried out to examine Au-catalyzed protodecarboxylation. Very recently Nolan et al reported the first example of the Au(I)-mediated decarboxylation of aromatic acids [12]. Surprisingly, the products are not protonated because the reaction stops at the metallation (i.e.…”
Section: Decarboxylative Aurationmentioning
confidence: 97%
“…Dies ist üblicherweise -wie in allen bisherigen Fällen beschrieben -aufwändig, und häufig ist es nçtig, den Metallkomplex zu hydrolysieren, was eine Katalyse unmçg-lich macht. [132] Nolan et al zeigten ebenfalls, dass analoge Kupferkatalysatoren ähnliche Aktivitäten aufweisen und erweiterten ihre Studien auf andere Substrate mit sauren Element-Wasserstoff-Bindungen, wie Imidazole, was zu einer N-Carboxylierung N-heterocyclischer Verbindungen führte. [133] Zahlrei- den.…”
Section: Katalysierte Synthese Von Carbonsäuren Aus Olefinen Und Co 2unclassified